New Faces of Indonesian Sufism: A Demographic Profiles of Tarekat Qodiriyyah-Naqsyabandiyyah, Pesantren Suralaya, in the 1990s - Day Howell, Julia (Association for the Publication of Indonesian and Malaysian Studies Inc., 2002)
Though once doubted, there is now a growing recognition of continuing importance of Sufi currnets in Indonesian Islam. Not only is there increasing acknowledgement that much of what was once read as 'Hindu-Buddhist' in Indonesian popular and court ritual is actually Sufi,with close parallels in other Muslim countries (Hodgson 1974, 551; Woodward 1989), but there are a number of recent reports that more specialised Sufi practices and institutions are enjoying remarkable popularity (Hasan 2001; Hasbullah 2000; Van Bruinessen 1992). These reports concern not just modern adaptations of Sufism through private Muslim educational institutes, formally organised prayer groups, TV programs, internet-mediated religious education, workshops and the like, but traditional Sufi orders (tarekat).